PEGylated nanomedicines: recent progress and remaining concerns. (January 2014) - Vllasaliu, Driton; Fowler, Robyn; Stolnik, Snow
<x xml:space="preserve">Abstract</x> Introduction: Recent biopharma deals related to nanocarrier drug delivery technologies highlight the emergence of nanomedicine. This is perhaps an expected culmination of many years of research demonstrating the potential of nanomedicine as the next generation of therapeutics with improved performance. PEGylated nanocarriers play a key role within this field. Areas covered: The drug delivery advantages of nanomedicines in general are discussed, focusing on nanocarriers and PEGylated nanomedicines, including products under current development/clinical evaluation. Well-established drug delivery benefits of PEGylation (e.g., prolonged circulation) are only briefly covered. Instead, attention is deliberately made to less commonly reported advantages of PEGylation, including mucosal delivery of nanomedicines. Finally, some of the issues related to the safety of PEGylated nanomedicines in clinical application are discussed. Expert opinion: The advent of nanomedicine providing therapeutic options of refined performance continues. Although PEGylation as a tool to improve the pharmacokinetics of nanomedicines is well established and is used clinically, other benefits of 'PEGnology', including enhancement of physicochemical properties and/or biocompatibility of actives and/or drug carriers, as well as mucosal delivery, have attracted less attention. While concerns regarding the clinical use of PEGylated nanomedicines remain, evidence suggests that at least some safety issues may be controlled by adequate designs of nanosystems.